FONEM BAHASA MOI RAGAM KELIN DI DISTRIK KLAILI KABUPATEN SORONG - Agustinus G. Gifelem; Frenny S. Pormes (Jurnal Akrab Juara, 2019)
This study aims to analyze the Moi Variety of Kelin Language Phonemes found in the Sorong District located in the Klaili District of Klaili village. Data were analyzed using a qualitative approach. Based on the analysis conducted, it was found MoiRagamKelin language vowel and consonant phonemes which varied based on the raw data obtained, so the data was classified and analyzed so that it can be clearly determined that there is a Moi language phoneme of Kelin variety consisting of five (5) vocals phonemes and four twelve (14) consonant phonemes, each of which has sound contrast, sound variations, and Moi language tribal patterns.